PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS XI SMAN 19 MAKASSAR - Wiwi Handayani Lili; Idawati; Nurhusna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve the news text writing skills of grade XI.3 students at SMAN 19 Makassar through the implementation of the Discovery Learning model. The method used is Classroom Action Research (CAR) conducted in two cycles based on the Kemmis and McTaggart spiral model, covering the stages of planning, action, observation, and reflection. The subjects were 26 students, with data collected through writing tests and classroom observation and analyzed qualitatively. The results show that Discovery Learning significantly improved students’ writing skills. In the pre-cycle, the average score was 68, with only 27% of students reaching the minimum mastery criterion (KKM ≥ 75). After Cycle I, the average score rose to 80, with 81% of students achieving mastery, and in Cycle II it reached 88, with all students (100%) meeting the standard. The greatest improvement occurred in the completeness of the 5W+1H elements, followed by gains in text structure, linguistic rules, and news content. It is concluded that the Discovery Learning model is effective in improving students’ news text writing skills.Keywords: Discovery Learning, writing skills, news text